Peningkatan Produktivitas Pembelajaran Daring Saat Pandemi melalui Manajemen Penyimpanan Pengelolaan Tugas Sekolah Menggunakan Google Drive - Noryani Noryani; Ahmad Maulana Irfanudin; Ratih Andalusi; Erlita Kurniawaty (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities are carried out at SDI Nurul Hidayah. The main problem faced by partners is the process of implementing Distance Learning (PJJ) which was previously announced by the South Tangerang city government, which in its implementation is still found many difficulties from the school and especially the guardians of students who accompany their children to study from home. Solutions given to Partner Problems, SDI Nurul Hidayah who are teachers and students as well as accompanying parents, for Distance Learning (PJJ). Therefore, Pamulang University Lecturers, especially the Management Study Program, collaborated with SDI Nurul Hidayah by providing practical training through online media via video conference media with a zoom application that carried the theme of using Google Drive as online storage media. By holding this activity, it is hoped that it can help them to launch the process of teaching and learning activities that are carried out online. As well as providing debriefing for the school and all its implementers regarding one of the online learning media directly through practice and tutorials.